Association of individual and neighbourhood socioeconomic status with physical activity and screen time in seventh-grade boys and girls in Berlin, Germany: a cross-sectional study. Issue 12 (28th December 2017) - Krist, Lilian; Bürger, Christin; Ströbele-Benschop, Nanette; Roll, Stephanie; Lotz, Fabian; Rieckmann, Nina; Müller-Nordhorn, Jacqueline; Willich, Stefan N; Müller-Riemenschneider, Falk
Abstract : Objectives: Few studies have explored the impact of neighbourhood socioeconomic status (SES) on health behaviours in youths in Germany. Our aim was to investigate the association of individual and neighbourhood SES with physical activity (PA) and screen time (ST) in students aged 12–13 years in Berlin. Design: Cross-sectional study. Setting: Secondary schools (high schools and integrated secondary schools) in Berlin, Germany. Participants: A total of 2586 students aged 12–13 years (seventh grade). Main outcome measures: Sociodemographics, anthropometric data and health behaviours were assessed by self-report during classes. Primary outcome was the association of individual and neighbourhood SES with meeting daily PA and exceeding daily ST recommendations. Students' characteristics were described with means or percentages. Comparisons were performed using generalised linear mixed model yielding ORs with 95% CIs. Results: Mean (±SD) age was 12.5±0.5 years, 50.5% were girls and 34.1% had a migrant background. When adjusting for individual covariates, associations of low versus high individual SES were 0.85 (0.48; 1.52) for PA and 2.08 (1.26; 3.43) for ST. Associations of low versus high neighbourhood SES were 1.76 (1.12; 2.75) for PA and 1.54 (1.10; 2.17) for ST. After additional adjustment for school type and school neighbourhood SES, associations comparing low versus high individual and neighbourhood SES were attenuated for PA (individual SES 0.74 (0.41; 1.33) and neighbourhood SES 1.51 (0.93; 2.46)) and ST (individual SES 1.88 (1.12; 3.14) and neighbourhood SES 1.40(0.98; 2.00). Conclusions: Lower individual and neighbourhood SES were associated with higher ST. Lower neighbourhood but not individual SES was associated with higher PA. After consideration of school type and school neighbourhood SES associations were attenuated and became insignificant for the relationship between neighbourhood SES, PA and ST. Further research is warranted to unravel the complex relationships between individual SES, neighbourhood SES and school environment to develop more targeted health promotion strategies in the future.